2009
DOI: 10.1021/ma900050a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Polymer Adsorption from Bulk Solution onto Planar Surfaces

Abstract: Polymer adsorption of uncharged homopolymers onto planar surfaces has been investigated by employing a coarse-grained bead-spring polymer model using simulation techniques. Polymer solutions of two different densities and polymers of two different contour lengths have been examined. The dynamics of the adsorption process appearing in systems composed of a polymer solution placed near attractive, but initially polymer-free, surfaces were determined by Brownian dynamics simulations and equilibrium properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 26 publications
5
55
0
Order By: Relevance
“…STM allows the determination of the chiral angle and the polymer spacing along the nanotube. For DNA and a (6,5) tube the angle and distance were $63 and $3.3 nm, respectively, which agreed well with computer simulations of the structure. For poly(3-hexylthiophene) the angle and distance were $45 and $1.7 nm, respectively.…”
Section: Reviewsupporting
confidence: 79%
See 1 more Smart Citation
“…STM allows the determination of the chiral angle and the polymer spacing along the nanotube. For DNA and a (6,5) tube the angle and distance were $63 and $3.3 nm, respectively, which agreed well with computer simulations of the structure. For poly(3-hexylthiophene) the angle and distance were $45 and $1.7 nm, respectively.…”
Section: Reviewsupporting
confidence: 79%
“…This change is quantified by the radius of gyration in the parallel direction relative to that in the perpendicular direction. Simulations 5,6 indicate that the radius of gyration in the perpendicular directions can be 1-2 orders of magnitude lower than that in the parallel direction; however the three-dimensional radius of gyration, which is easily measurable, will show little change because the sum of the square of the two radii of gyration is approximately constant.…”
Section: Dissolution-dispersionprecipitationmentioning
confidence: 99%
“…30 There are several theoretical studies in the literature available on this topic. [31][32][33] However, there are substantial problems in studying the kinetics of the process experimentally in a very short time scale. [34][35][36] The kinetic data presented below can be described as those from a bimodal process in the way proposed by Chiang et al 37 Our data agree with the results previously reported for other polyelectrolyte systems.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Adsorption of synthetic polymers and proteins to solid surfaces is of interest for many industrial and biomedical applications [1-4]. Aiming to understand the driving forces of such interactions, adsorption processes have been studied with a variety of techniques [5] including reflectometry [6], quartz crystal microbalance [7], atomic force microscopy [8], and fluorescence microscopy [9].…”
Section: Introductionmentioning
confidence: 99%